Pengaruh Fasilitas Kerja dan Lingkungan Kerja Non Fisik Terhadap Kinerja Karyawan PT Xylo Solusi Indonesia - Cahya dianti, Teti; Ety Nurhayaty (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2025)
This study aims to examine the partial and simultaneous effects of work facilities and non-physical work environment on performance. The research was conducted at PT Xylo Solusi Indonesia. This study uses a descriptive quantitative research approach. The research applied a saturated sampling method, where all 32 employees were taken as the sample, and data analysis was conducted using SPSS version 25. The results of this study show that work facilities have a positive and significant effect on performance, while the non-physical work environment has a positive but insignificant effect on employee performance. Meanwhile, both work facilities and the non-physical work environment simultaneously have a positive and significant effect on performance. These findings provide insights for stakeholders to evaluate and improve business strategies within the company.